Capacity Building Challenges of Municipal Councillors in the Mangaung Metropolitan Municipality in the Free State Province - Taaibosch, T A; van Niekerk, T (Administratio Publica, 2017)
Through the introduction of the relatively new council structures for metropolitan municipalities in South Africa, and the new mandate for municipalities, the traditional role of councillors has broadened to encompass additional responsibilities and functions. Therefore, municipal councillors (proportional public representative (PR) councillors) require specific competencies and skills in order to ensure the effective operation of their local municipality. The efficacy of municipal councillors in respect of service delivery is increasingly being questioned in the wake of recent service delivery protests and negative reporting on the state of the local government sphere. The current state of affairs relating to municipal councillors raises numerous questions about the required skills and capacity building challenges to successfully execute their mandate. The aim of this article is to further investigate by means of an interview schedule the training and capacity building challenges of municipal councillors in the Mangaung Metropolitan Municipality in the Free State Province. A qualitative research methodology is adopted for the realisation of the above aim. An interview schedule was utilised as a tool that contains the predetermined questions prepared in order to acquire the insight, knowledge and application of the persons involved and familiar with the municipal councillor processes and challenges. The requirements, purpose, roles, functions and mandate of municipal councillors will be provided. The findings of the empirical study will be provided, followed by specific recommendations pertaining to capacity building and training initiatives to address these challenges.
Published Article